Fatty acid composition and physicochemical properties of Malaysian castor bean Ricinus communis L. seed oil - Jumat Salimon; Dina Azleema Mohd Noor; A. T. Nazrizawati; M. Y. Mohd Firdaus; A. Noraishah (Universiti Kebangsaan Malaysia, 2010)
The crude oil of Malaysian castor bean Ricinus communis L. seed was extracted by Soxhlet method using hexane. The physicochemical characteristics of castor bean oil were evaluated. The results showed that Malaysian castor seeds contain a relatively high percentage of total lipids content; 43.3% (per dry weight), high iodine value (84.5 mg/g) and saponification value (182.96 mg/g). The seed oil moisture content, acid value and free fatty acid percentage (% FFA) were 0.2%, 4.88 mg/g and 3.4%, respectively. The unsaturated fatty acids (UFA) content were 97.5% of the total fatty acids composition. Ricinoleic acid comprises over 84% while other fatty acids present were linoleic (7.3%), oleic (5.5%), palmitic (1.3%), stearic (1.2%) and linolenic (0.5%), respectively. Five types of castor bean seed oil triacylglycerols were identified as triricinolein, RRR (84.1%), diricinoleoylstearoylglycerol, RRS (8.2%), diricinoleoyloleoyl-glycerol, RRO (5.6%), diricinoleoyllinoleoylglycerol, RRL (1.2%) and diricinoleoylpalmitoyl-glycerol, RRP (0.9%), respectively.